THE EFFECTIVENESS OF PROBLEM BASED LEARNING MODEL TO INCREASE PHYSICS COGNITIVE AND PSYCHOMOTOR ACHIEVEMENTS THROUGH LABORATORY ACTIVITY IN HOOKE LAW LESSON - Sri Wahyuningsih Leli; Sumardi Yosaphat (Jurnal Pendidikan Fisika, 2016)
This research was performed with the two purposes below. (1) Discover if there was difference in increasing cognitive and psychomotor achievements between students who were taught by using problem based learning (PBL) through experiment and students who were taught by using direct instruction model with experiment method. (2) Discover the effectiveness of problem based learning model to increase cognitive and psychomotor achievements through experiment activity in Hooke Law lesson.The method of this research was quasi experiment by using pretest-posttest control group design. This research was conducted in SMA Negeri 5 Yogyakarta. The populations of this research are the students of science 11th grade of SMA Negeri 5 Yogyakarta which consist of 6 classes. Sampling technique used cluster random sampling. The classes used in this experiment were 11th science 1 and 11th science 3. The instruments of this research were lesson plan, student worksheet, test of cognitive achievement which consist of two types, i.e. essay test and psychomotor observation sheet in form of rating scale. The data analysis method to test the hypothesis is MANOVA test. The results of this research show the two conclusions below. (1) There was difference in increasing cognitive and psychomotor achievements between students who were taught Hooke Law by using PBL model through experiment activity and the students who were taught by using direct instruction model through experiment method. (2) PBL model through experiment activity was more effective to increase cognitive and psychomotor achievements then direct instruction learning model and experiment method.Key words: PBL model, direct instruction, experiment method, cognitive and psychomotor achievements.